Critical success factors in university-industry collaboration: a bibliometric analysis (Research, Society and Development, 2021)
Considering the technological development, and particularly the global pandemic of COVID-19, it is essential to align universities and companies as agents in the transformation of society. However, a portion of academic research results does not find application in the productive sector. To better understand such (dis)connection, this study aims to verify in the scientific literature the critical success factors proper to the collaboration between universities and companies. Therefore, a bibliographic survey was carried out in the Scopus and Web of Science databases, considering the period 2000-2020 as temporality. From a quantitative point of view, a bibliometric analysis is presented regarding the year of publication, origin, thematic categories, authorship and co-citation networks, and with a qualitative character, through content analysis, critical factors were identified, with emphasis on trust, commitment, assumption of risks, realistic and well-defined objectives, managerial engagement of project coordinators, university reputation, previous experience in collaboration, communication and organizational culture.